Sophia Galier: capstone - Galier, Sophia, artist (Colorado State University. Libraries, 2025)
The artist's statement: Through oil narrative paintings, I aim to tell a story of sacrifice. We see the figure perform various forms of sacrifice, becoming increasingly bloodthirsty and hungry. She builds upon her sacrifices to appease. But what is she aiming to please? And why is she willing to lose her humanity for it? That is for the viewer to discover. I am greatly influenced by the horror novels I love so deeply, and it is where I gain most of the inspiration for my work. I am also influenced by true crime stories as well as my Texas upbringing. Taking elements of the folk stories I grew up hearing and the landscape that surrounded my upbringing, I design the environment and factors of the story. I also take influence from Christianity and Paganism, blending the two to create almost religious images. I work layer by layer, slowly building up details and values. I block in my colors and values and then blend them out together at once, letting it dry and coming back in with a new layer. What makes my work unique is the use of myself and my loved ones as references. This makes my work very personal to me and combative for the viewer. As you view the pieces, ask yourself: what is the story that's happening here? Whom is she trying to appease? And finally, what are you willing to sacrifice?
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting